Zebrafish as a model for human epithelial pathology - Ahmed Abu-Siniyeh; Moayad Khataibeh; Walid Al-Zyoud; Majed Al Holi (Laboratory Animal Research)
Abstract Zebrafish (Danio rerio) have emerged as an influential model for studying human epithelial pathology, particularly because of their genetic similarity to humans and their unique physiological traits. This review explores the structural and functional homology between zebrafish and human epithelial tissues in organs, such as the gastrointestinal system, liver, and kidneys. Zebrafish possess significant cellular and functional homology with mammals, which facilitates the investigation of various diseases, including inflammatory bowel disease, nonalcoholic fatty liver disease, and polycystic kidney disease. The advantages of using zebrafish as a model organism include rapid external development, ease of genetic manipulation, and advanced imaging capabilities, allowing for the real-time observation of disease processes. However, limitations exist, particularly concerning the lack of organs in zebrafish and the potential for incomplete phenocopy of human conditions. Despite these challenges, ongoing research in adult zebrafish promises to enhance our understanding of the disease mechanisms and regenerative processes. By revealing the similarities and differences in epithelial cell function and disease pathways, this review highlights the value of zebrafish as a translational model for advancing our knowledge of human health and developing targeted therapies.